2014
DOI: 10.11120/pblh.2013.00021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nurse Lecturer Situated within a Practice–Education Partnership

Abstract: Aims and Objectives: To critically explore the nurse lecturers role situated within a practice-education partnership and to identify practice recommendations to operate the role within the context of a partnership in the future.Background: Practice-education partnerships are increasing being developed to operationalize the healthcare policy that advocates partnership working between Academic Education Institutions and healthcare organizations to educate and train the nurse workforce and to develop nursing. A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Likewise, the participants reported that the nurse educators’ supervisory approach, expectations, demands and, moreover, what they emphasised during the assessment discussions could vary, which was described by students as adverse. Indeed, previous research indicates that the nurse educator’s role in clinical practice is not clearly defined and varies by institution and country [ 39 , 40 ]. In the United Kingdom (UK), national standards for the clinical education and mentorship have existed for many years [ 41 , 42 ], and most recently these have been updated to reflect the shift in UK nursing from mentorship to supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the participants reported that the nurse educators’ supervisory approach, expectations, demands and, moreover, what they emphasised during the assessment discussions could vary, which was described by students as adverse. Indeed, previous research indicates that the nurse educator’s role in clinical practice is not clearly defined and varies by institution and country [ 39 , 40 ]. In the United Kingdom (UK), national standards for the clinical education and mentorship have existed for many years [ 41 , 42 ], and most recently these have been updated to reflect the shift in UK nursing from mentorship to supervision.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the 1860s Florence Nightingale set up the first School of Nursing that adopted a largely unregulated system to provide 'on the job' training. The tripartite partnership agreement between administrators (matron), doctors and nurses (Rivett 1988) was the collaborative training model she used to operationalise this apprentice style training (Leigh 2014). What is new in terms of apprenticeship models is the concept of D&HLAs.…”
Section: Introductionmentioning
confidence: 99%
“…Teaching and learning strategies that commonly promote opportunities to effectively communicate within the learning organisation are those that assist healthcare leaders to build relationships with the right people and to demonstrate exemplary leadership (Kouzes and Posner 2012). The notion of structural empowerment (Leigh 2014, Patrick et al 2011, Steinert, Goebel, and Rieger 2006 may be achieved through the leader demonstrating effective sharing of information through all tiers of their organisation. A notion often connected to this is the need to develop a shared purpose (Manley, Parlour, and Yalden 2013) which is a key activity of practice development work.…”
Section: Healthcare Leadership Developmentmentioning
confidence: 99%